Meta-analysis of probiotic metabolites in the prevention of gestational weight gain and postpartum weight retention - Jia, Xuyue; Sun, Shuangyan; Ci, Zhimin (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionMaternal weight gain and metabolic health during pregnancy significantly influence both short- and long-term outcomes for mother and child.MethodsThis systematic review and meta-analysis included data from 46 randomized controlled trials (RCTs), comprising over 12,500 pregnant women across diverse populations.ResultsProbiotic supplementation, especially multispecies formulations, initiated in the first trimester led to a mean reduction in gestational weight gain (GWG) of 1.25 kg (95% CI: −1.78 to −0.72 kg; p < 0.001) compared to controls. Furthermore, postpartum weight retention was reduced by an average of 1.05 kg (95% CI: −1.53 to −0.58 kg; p < 0.001) when probiotic use extended into the postpartum period. Significant improvements were also observed in metabolic markers: fasting glucose decreased by 0.22 mmol/L, Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) scores decreased by 0.45 units, and total cholesterol and Low-density lipoprotein (LDL) were reduced by 0.28 and 0.17 mmol/L, respectively.DiscussionThese effects were mediated by the modulation of gut microbiota, promoting the production of beneficial short-chain fatty acids (butyrate) and reducing systemic inflammation through increased levels of microbial-derived metabolites, including conjugated linoleic acids and indole-3-propionic acid, which enhance gut barrier integrity and metabolic resilience. The heterogeneity in strains, dosage, and duration and pooled analysis consistently favored probiotic intervention. These findings support the use of probiotics as a safe, non-pharmacological strategy to improve metabolic outcomes during pregnancy. Future studies should focus on personalized probiotic interventions and long-term maternal–child health effects.